1990
DOI: 10.1210/endo-126-5-2635
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of the Glucocorticoid Receptor in Pancreatic β- Cells of the Rat*

Abstract: We used a monoclonal antibody against an epitope located in the N-terminal moiety of the rat glucocorticoid receptor to identify the glucocorticoid receptor-containing cells in the rat pancreas. Monospecific polyclonal antisera against insulin, glucagon, somatostatin, and amylase were applied to serial sections in colocalization studies to identify the respective endocrine and exocrine cells. Glucocorticoid receptor immunoreactivity was exclusively present in nuclei and cytoplasm of the beta-cells of pancreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…Species differences in expression may be important and our observations with regard to GR abundance would endorse this. We observed GR immunoreactivity throughout the whole murine islet and not exclusively in the beta cells as reported in rat tissue [7].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Species differences in expression may be important and our observations with regard to GR abundance would endorse this. We observed GR immunoreactivity throughout the whole murine islet and not exclusively in the beta cells as reported in rat tissue [7].…”
Section: Discussionsupporting
confidence: 77%
“…GR immunoreactivity has been found to be exclusively present in the nuclei and cytoplasm of beta cells of rat pancreatic islets [7]. The effects of glucocorticoid on insulin secretion are dependent upon the dose and duration of administration [8].…”
mentioning
confidence: 98%
“…GR are present in the cells of the adult pancreas (Fischer et al 1990) and glucocorticoids have been shown to regulate pancreatic development (Rall et al 1977, Hill 1999. Furthermore, it has been shown previously that glucocorticoids inhibit insulin secretion from cultured adult mouse islets (Lambillote et al 1997).…”
Section: Discussionmentioning
confidence: 98%
“…After dexamethasone treatment, alterations in beta-cell gene expression presumably occur in response to the metabolic perturbations but the steroid could act also by a direct effect on the beta cell because rat beta cells express glucocorticoid receptors [72]. The differential effect on IAPP and insulin gene expression could be explained by the presence of a negative regulatory element in the insulin gene promoter, which is lacking in the IAPP gene promoter and which binds dexamethasone [73].…”
Section: Potential Mechanisms Of Differential Expression Of Iapp and mentioning
confidence: 99%